A weaker Russia: Serious repercussions for EU-Russia relations - Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2011)
The EU's current policy towards Russia assumes that the Kremlin is interested in a comprehensive national modernisation programme and has the power to put this into practice. But what if this assumption turns out to be incorrect? Numerous structural obstacles give grounds for scepticism that Russia will manage to implement such an endeavour. Without modernisation Russia will weaken, but will be unwilling to relinquish its international aspirations. The EU needs to prepare for a situation where the premises of its Russia policy no longer apply, and should lose no time in preparing a Plan B
Keywords: 320